2013
DOI: 10.3109/02688697.2012.752432
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic markers in gliomas – an update

Abstract: Gliomas are the most common primary central nervous system tumour seen in adults. There have been many advances over the last two decades as we widen our search for a molecular basis of gliomagenesis. Many biomarkers have been discovered to be important in the management of gliomas, including 1p19q co-deletion, MGMT promoter methylation, BRAF and IDH1 mutations. In this review, we attempt to summarise the available literature on these biomarkers and their use in the diagnosis and management of gliomas. We pay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
10
0
4
Order By: Relevance
“…Therefore, MGMT is critical for the protection of normal cells from exogenous carcinogens. Its inactivation by promoter hypermethylation plays an important role in tumorigenesis in several types of tumors including CRC [8][9][10][11][12][13]. An ideal study designed to address this question would be to perform a serial analysis of the whole process from adenoma to carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MGMT is critical for the protection of normal cells from exogenous carcinogens. Its inactivation by promoter hypermethylation plays an important role in tumorigenesis in several types of tumors including CRC [8][9][10][11][12][13]. An ideal study designed to address this question would be to perform a serial analysis of the whole process from adenoma to carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Pero no se ha observado este marcador en otros tumores del sistema nervioso central como neurocitomas, ependimomas, astrocitoma pilocítico y meduloblastoma entre otros 2,19 .…”
Section: Isocitrato Deshidrogenasaunclassified
“…En la literatura está descrito un aumento de la supervivencia global y tiempo libre de la enfermedad después de la cirugía en paciente portadores de la mutación de la IDH1 2,7,11,14,17,21,[30][31][32][33] . La supervivencia media varía entre los 16 a 42,9 meses según los estudios consultados 2,7,11,14,17,21,[30][31][32][33] .…”
Section: Figura 3 -Comparativa Entre El Metabolismo Celular Con La Idunclassified
See 1 more Smart Citation
“…12,21 Patients with malignant astrocytoma with IDH1 mutations have nearly twice as long, or even 10 times longer, median overall survival compared with those without mutations. 3,34 A recent study also revealed that refinement of the classification of the 3 most common types of brain tumors could be achieved by telomerase reverse transcriptase promoter and IDH1 mutation status.…”
Section: Feasibility Of Microfluidicsmentioning
confidence: 99%